PADAT POPULASI DAN PERSENTASE SERANGAN Paracoccus marginatus Wiliams and Granara de Willink (HEMIPTERA: PSEUDOCOCCIDAE) PADA PERTANAMAN PEPAYA MONOKULTUR DAN POLIKULTUR DI KECAMATAN DIMEMBE KABUPATEN MINAHASA UTARA - Riedel Lolong; Juliet M.E. Mamahit; Odi R. Pinontoan; Betsy A.N. Pinaria (COCOS, 2014)
ABSTRACTPapaya is a fairly widely cultivated plant in Indonesia. Fruits of the plant are most commonly used for directly consumption, while the flowers and leaves use as a vegetable. Lately, there are new pests that attack papaya plants, which is papaya mealybug Paracoccus marginatus. This research aimed to find out the population and percentage of the P. marginatus attack on papaya cultivated by monoculture and polyculture. The research was conducted in District of Dimembe, North Minahasa Regency. The research was carried out for 7 months, March to September 2014. This research used a survey methods. Three villages used as sampling sites were in Matungkas Village, Laikit Village and Dimembe Village. Each village was taken three locations of papaya cultivated consisted of monoculture and polyculture. Observations percentage of the attacks mealybugs done visually by symptom. Parts of plants observed were leaf, stem, petiole and fruit.The highest population of P. marginatus found in papaya plantation monocultures in the Matungkas Village with an average of 3669,00 mealybug, followed by the population in the Village of Dimembe 3205,33 mealybug and least found in the Laikit Village with 1379,22 mealybug, while the highest population of P. marginatus in papaya plantation polyculturefound in the Matungkas Village with an average 495,67 mealybug, then in the Laikit Village with an average 423,11 mealybug and the lowest population found in the Dimembe Village with an average 314,00 mealybug. Papaya plantation in Matungkas Village was the highest location attacked and the most parts of the plant that were attacked was leaves with a percentage of 93,33% on the location of monoculture plantations and 63,33% in polyculture plantations location.Keywords: Papaya, Paracoccus marginatus, Population and Percentage of attacks